Tinjauan Implementasi Etika Bisnis Islami di Galery Muslim Hidayatullah Kota Jambi - Siti Aminatun Rizki; AA Miftah (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2018)
This study aims to bring together the theory of Islamic business ethics and its practice in the field. This study took a sample gallery Muslim hidayatullah in the city of Jambi. Descriptive methods and content analysis were used to answer previous research questions. the result is that Islamic business ethics in the company has not been fully implemented, there are some that have not been applied, namely the essential principle in business is honesty, hospitality, there are still employees serving buyers not in accordance with Islamic business ethics. copy that other principles of business ethics have been applied properly